Prospective Study on the Opening of the Manado–Jeddah International Route - Kurniawan S. Abas; Lucia I. R. Lefrandt; Semuel Y. R. Rompis (Journal of Social Research, 2025)
The opening of the international flight route between Manado and Jeddah presents a strategic opportunity to enhance connectivity between eastern Indonesia and major centers of religious activities, trade, and global mobility in the Middle East. This study aims to analyze the prospects of establishing this route through a comprehensive approach that encompasses market, operational, economic, and policy aspects. Data were obtained through a combination of demand analysis for Umrah and Hajj travel from North Sulawesi and surrounding regions, evaluation of airport capacity and supporting infrastructure readiness, as well as an economic feasibility assessment based on projected operational costs and airline revenue potential. The results indicate that the demand for religious travel shows a significant upward trend, providing a strong market potential. Additionally, Sam Ratulangi International Airport is considered capable of supporting medium-haul flight operations with several technical adjustments. Economically, the route has the potential to generate profits for airlines if fare strategies, flight frequency, and market segmentation are properly optimized. This study concludes that the opening of the Manado–Jeddah route holds promising prospects but requires synergy among airlines, airport authorities, and regional governments in infrastructure development and market promotion.